THU0522 Correlation between serum calprotectin (MRP8/14), clinical and ultrasound assessment in patients with juvenile idiopathic arthritis. (15th June 2017) - Romano, M; Gerloni, V; Gattinara, M; Lucia, O De; Meroni, PL
Abstract : Background: MRP8/14 (also known as calprotectin) has been widely studied as potential predictor of disease activity and response to treatment in inflammatory diseases. In Juvenile Idiopathic Arthritis (JIA), MRP8/14 levels are highly predictive of disease flares in systemic JIA. In a more heterogeneous group of JIA patients (pts), MRP8/14 levels have been shown to predict response to MTX. High levels of baseline MRP8/14 are associated with good response to anti-TNF treatment, whereas elevated MRP8/14 levels at time of discontinuation are associated with higher chance to flare. In clinical practice, ultrasound could be usefull to define the state of disease activity. Indeed, PD-US assessment of synovial vascularization has been shown to be more sensitive than serum markers of inflammation in the identification of active disease in JIA. Objectives: To explore the association between calprotectin, clinical and US assessment in JIA pts. Methods: A total of 30 consecutive pts (aged under 18 years) with oligo or poly JIA were assessed by US, clinical examination and MRP8/14 serum levels. Serum MRP8/14 was measured by ELISA in all pts and in 20 age matched healthy controls. Ultrasonographic B-mode and power Doppler assessment of 44 joints each pts were performed. Patients were evaluated using Wallace criteria. Results: 30 consecutive non systemic JIA pts (F 18) were evaluated: 13 persistent and 8 extended oligoarticular, 6 polyarticular (1 RF positive), 2 ERA, 1 psoriatic JIA. Median age at disease onset was 10.6 yrs (mean 10.8, range 2–16). Mean disease duration was 5.4 yrs (range 0.1–15.9). Mean active joints was 2 (range 0–26). 14 pts were active according to Wallace criteria and 16 pts were active according to US evaluation. Ultrasonographic B-mode and power Doppler assessment was significantly correlated with clinical examination (Mcnemar test p=0.683, Cohen's K 0.602). The majority of our enrolled pts were in phase of oligoarticular involvement with minimal disease activity (median active joints=0). No statistically significant difference in serum MRP8/14 was found between all JIA pts and healthy controls (p=0.33). No statistically significant difference in serum MRP8/14 was found between active (according to clinical examination) JIA pts and healthy controls (p=0.69) and between inactive JIA pts and healthy control (p=0.23). Concentrations of MRP8/14 in active and inactive pts according to Wallace were not significantly different (p=0.75). No statistically significant difference in serum MRP8/14 was found between active and inactive pts according to US assessment (0.85). Only 6 pts (4 out of 6 with polyarticular course) showed calprotectin levels higher than normal. We found a correlation between calprotectin and CRP (Spearman r 0.4380, p=0.01) and between calprotectin and ESR (Spearman r 0.3800, p=0.05). Conclusions: To our knowledge this is the first study to examine the correlation between MRP8/14 levels, clinical and US assessment in JIA. Serum levels of MRP8/14 (a biomarker of activation of the innate immune system) are not significatively different in oligoarticular JIA from healthy controls. Calprotectin high levels, could be related with a poliarticular disease either in clinical activity or in subclinical remission. However our study need to be extended to a larger number of pts followed prospectively. Disclosure of Interest: None declared